2021
DOI: 10.1111/2047-3095.12337
|View full text |Cite
|
Sign up to set email alerts
|

Concept analysis of perceived health from the perspective of rural adults in China

Abstract: Purpose: This paper aims to clarify the concept of perceived health from the perspective of rural adults in China.Methods: Walker and Avant's concept analysis was applied.Findings: Perceived health from rural adults in China is a subjective assessment of their health status, which is deeply affected by Chinese traditional culture and being in a rural environment.Conclusions: Most rural adults in China could perceive their health as good or poor, however, rural areas have disadvantages in health care, geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In rural areas, the population is often older and tends to suffer more from chronic diseases than do residents of non-urban regions [6][7][8][9][10]. Consequently, rural primary care has unique challenges, often involving complex medical cases and limited resources [6,[11][12][13][14][15][16][17]. To tackle these problems, previous studies have suggested various approaches, such as strengthening multiprofessional collaboration [18][19][20][21][22][23], establishing remote pharmacy services [18,19], and developing public health programs aiming at medication process evaluation and enhanced safety of care providers [24,25].…”
mentioning
confidence: 99%
“…In rural areas, the population is often older and tends to suffer more from chronic diseases than do residents of non-urban regions [6][7][8][9][10]. Consequently, rural primary care has unique challenges, often involving complex medical cases and limited resources [6,[11][12][13][14][15][16][17]. To tackle these problems, previous studies have suggested various approaches, such as strengthening multiprofessional collaboration [18][19][20][21][22][23], establishing remote pharmacy services [18,19], and developing public health programs aiming at medication process evaluation and enhanced safety of care providers [24,25].…”
mentioning
confidence: 99%